Consumption of Iron Tablets and Hemoglobin Levels of Anemic Pregnant Women: A Meta-Analysis Study - Rani Nurfitra; Demsa Simbolon (Poltekkes Kemenkes Palu, 2025)
Iron Tablet Suplement (ITS) Consumption is expected to prevent anemia with increased hemoglobin levels. The 2023 Indonesian Health Survey report shows that 27.7% of pregnant women in Indonesia experience anemia which will have an impact on pregnancy and childbirth complications. The study aims to determine the effect of ITS consumption on increasing hemoglobin levels in anemia pregnant women, so that it can prevent complications of pregnancy, childbirth and the birth of stunted babies. This study uses meta-analysis using the random effect model method. Articles accessed from Google Scholar and PubMed databases. The selection of articles used the PICOTS framework, which included the population of pregnant women, ITS consumption interventions, comparison with the control group that did not consume ITS, the outcome of increasing hemoglobin levels, and the research design in the form of a quasi-experimental study. The inclusion criteria are research articles published in 2010–2022, using a quasi-experimental design, full text available, and mean difference data available. The search used the keywords